TYPY PRZEBIEGU PENTADOWYCH WSPÓŁCZYNN IKÓW STANU WODY JEZIOR NIŻU POLSKIEGO - Plewa, Katarzyna (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2018)
The purpose of the research is to determine the types of course of the coefficients of water stages on pentads on the hydrological year. The research distinguishes five main types and seven subtypes of pentad coefficients of the water stages of lakes in Poland in the average annual cycle. For the analysis, the daily values of water levels of 75 lakes located in the Polish Lowlands in years 1976-2015 were used. The data were obtained from the Institute of Meteorology and Water Management – National Research Institute. For each lake, the coefficient of water stages, for all 73 pentads of the hydrological year, was calculated. Pentadic values of water stage coefficients were the basis for hierarchical grouping of the lakes using Ward’s method. On the basis of dendrogram analysis, 5 main groups of lakes with a different coefficient of water storage in the annual cycle were distinguished – so-called types of the course of pentad coefficient of water stages. The types distinguished differ in the beginning, end and duration of high and low water stages, as well as the variability of the coefficient of water stage in pentads of the hydrological year. Type 1 – with a small range of W coefficient parameter changes throughout the year is characteristic of coastal lakes, in type 2 lakes, high water stages are observed in the summer-autumn period, low stages in spring. In the remaining types, high water stages are usually observed in spring and low in the summer-autumn period.